Because the clients told us so. Issue 4 (18th December 2017) - Davis, Dana; Hawk, Mary; Winkler, Dana
Abstract : Purpose: Eliciting client narratives and creating community-informed interventions have been effective methods of engaging those who are unstably housed in care. Previous studies have shown that these approaches foster client empowerment and provide insight as to the importance of creating community-driven solutions. However, few studies report the impact of these methods on homeless people living with HIV. The purpose of this paper is to describe methods used to engage consumers in sharing their stories, including formative focus groups, qualitative interviews, and feedback from peer staff. Design/methodology/approach: Data for the case study were derived from program notes, board minutes, and feedback from founding board members of The Open Door. Two researchers who were involved with the program from its inception reviewed these data and then developed a schematic of the methods used to develop and inform the program itself. The authors determined that three methods were used to elicit client and community narratives to inform program decisions. These include a formative focus group that helped to structure and implement the program in its earliest stages; qualitative interviews, which helped to pinpoint effective program components and enabled the rapid expansion of the service delivery model; and feedback from peer staff, which has consistently allowed for the refinement and prioritization of services. Data were collected for the purposes of program development and improvement but since qualitative interviews were conducted by faculty affiliated with an academic institution, the institutional review board of that institution was consulted and the qualitative interviews were determined to be exempt from review. Findings: The focus group informed the authors that they wanted to live in their own apartments but have on-site supports. They also indicated that traditional housing program rules such as abstinence were too restrictive for them to navigate. In the qualitative interviews, the clients reported an increased sense of community with peers and peer staff members, which helped to reduce stigma. Second, residents reported that supportive services helped them to connect to and maintain in HIV clinical care. Third, residents reported that the representative payee services were a key factor in helping them improve housing and financial stability. Research limitations/implications: There are a number of limitations to this case study that demand the need for caution in interpreting results. Although the authors used several different methods to elicit client narratives and community feedback, sample sizes were small, control groups were not utilized, and data were specific to individuals receiving services through one housing program. Thus, results are not generalizable. In addition, the methods reported herein mix those conducted for the purposes of research (in-depth qualitative interviews) with others conducted specifically to inform program delivery and improvement (focus group and peer staff feedback). Thus, rigor is not equally applied across all methods. In addition, the individuals conducting research and authoring this paper were directly involved with the creation of the program and ongoing service delivery. Therefore, interviewer and reporting bias also present threats to validity. Practical implications: There are many strengths involved in utilizing the narrative feedback of the residents and peer staff to inform the practice. One is that this method is an incredibly cost-efficient way to assess client and program needs to inform intervention development and improvement. The results are also very transparent and easily translatable to the agency's everyday work. These methods are practical in both their approach to clients and their ability to be easily incorporated into the daily work of clients and staff. These methods allow for rapid application as results are immediate and feedback can be implemented quickly. Social implications: When seeking client and staff feedback, it is important to be cognizant of believing the client and recognizing that all people have their own personal perspectives, including their own version of the "truth." Eliciting this type of feedback puts individuals in a vulnerable place, so it is critical to guarantee their safety. All information solicited must be regarded in a positive light to inform improved service delivery and not as a means to receive information that "tells on" clients or peer staff. Feedback should be reviewed as an opportunity for learning and not as a mechanism for retaliation. Originality/value: The clients and staff have been significantly marginalized in the society. It is possible that having providers be kind and respectful to them and asking for their opinions is a very new experience which might make them feel grateful and more likely to be favorable in their responses. Clients may feel loyal to the program and be much more likely to speak of it positively. Regardless of these potential biases, the quantitative results of improved health outcomes published elsewhere indicate that the clients may not just be being nice, but may in fact be receiving interventions that are working.